Some Facts of Main Ethnic Groups' Ceremonial-Game Traditions in Their Theatrical Aspect in the Chuvash Republic - Veronika Y. Arestova (Publishing house "Sreda", 2020)
The article presents facts about ceremonial-game traditions of main ethnic groups living in Chuvash Republic, such as Chuvash, Russian, Tatar, and Mordovian. The purpose of the research was the survey of ceremonies, customs and celebrations which are kept in the present time in Chuvashia. The research was focused solely on theatrical aspect of rites or ceremonies where a person uses dressing up, masks, makeup, and acts for Mummers' plays. Furthermore, the research aimed to identify the mutual cultural influence of the above mentioned ethnic groups on each other. The field study was conducted using the methods of interviewing, observation with video and audio recording. The data were gathered from all of Chuvash Republic districts. In conclusion, it was established that mummering traditions are being revived in some rural areas of Chuvashia; traditions of mummering have not been changed since the second half of the XIX century, but people created new characters, especially in the second half of the XX century; the content of ceremonial-game traditions is fully demonstrates the worldview, mentality and value system of the main ethnic groups presented in Chuvashia.